Epidemiologic methods - Koepsell, Thomas D. (Oxford University Press, 2003)
The book's chapters are organized around three main themes: general concepts and methods of epidemiology; major study designs; and evaluating policies and programs. Collectively, these topics form the core material for a graduate-level course or course sequence in epidemiologic methods. Both authors are experienced epidemiologic researchers and have won multiple awards for effective teaching